Application of Moving Average for Forecasting The Amount of Electricity Distribution in The Mojokerto Region - Hanafi, M. Irfan (KH. A. Wahab Hasbullah University, 2022)
PT PLN Mojokerto is responsible for managing electricity distribution in the Mojokerto area. To effectively manage electricity distribution, accurate forecasting is crucial. Data plays a pivotal role in making decisions related to electricity distribution in Mojokerto. The primary objective of this research is to forecast the amount of electricity to be distributed in the area. Having an accurate forecast is essential for estimating future electricity distribution. The research utilizes the Moving Average model, a time series forecasting model. Data for the research is sourced from the Mojokerto statistical agency, covering the period from 2014 to 2020. By employing the Moving Average method, researchers can generate forecasts for the future. Additionally, the researchers calculate MSE (Mean Squared Error) and RMSE (Root Mean Squared Error) when using the Moving Average method.